2014
DOI: 10.1113/jphysiol.2014.271700
|View full text |Cite
|
Sign up to set email alerts
|

Activation of glycine receptors modulates spontaneous epileptiform activity in the immature rat hippocampus

Abstract: Key pointsr Taurine has a pro-and anticonvulsive effect on the immature hippocampus, depending on the dose.r The taurine effect is mediated by GABA A and glycine receptors. r The taurine effect can be partially mimicked by glycine. r Inhibition of glycine receptors has a weak proconvulsive effect on the immature hippocampus. r We conclude that an endogenous activation of glycine receptors by glycine or taurine contributed to the control of neuronal excitability in the immature hippocampus.Abstract While the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 62 publications
4
28
1
Order By: Relevance
“…In patients with temporal lobe epilepsy changes in hippocampal glycine receptor expression have been reported, suggesting dysregulation of glycinergic signaling in epilepsy (Eichler et al, 2008). In line with those findings activation of glycine receptors modulated spontaneous epileptiform activity in the immature rat hippocampus (Chen et al, 2014), whereas GlyT1 inhibitors demonstrated anticonvulsant properties in a rat maximal electroshock test (Kalinichev et al, 2010). However, the role of GlyT1 in human epilepsy and in clinically relevant rodent models of chronic epilepsy has not been studied to date.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…In patients with temporal lobe epilepsy changes in hippocampal glycine receptor expression have been reported, suggesting dysregulation of glycinergic signaling in epilepsy (Eichler et al, 2008). In line with those findings activation of glycine receptors modulated spontaneous epileptiform activity in the immature rat hippocampus (Chen et al, 2014), whereas GlyT1 inhibitors demonstrated anticonvulsant properties in a rat maximal electroshock test (Kalinichev et al, 2010). However, the role of GlyT1 in human epilepsy and in clinically relevant rodent models of chronic epilepsy has not been studied to date.…”
Section: Introductionsupporting
confidence: 80%
“…Glycine in the hippocampus combines unique properties to regulate network excitability through opposing roles of pre- and postsynaptic GlyRs (Chen et al, 2014; Eichler et al, 2008; Kirchner et al, 2003; Kubota et al, 2010; Winkelmann et al, 2014), and through activation of the glycine B site of the NMDAR (Black et al, 2009; Labrie and Roder, 2010; Mohler et al, 2008). Therefore, maintenance of glycine homeostasis might play a critical role in epilepsy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the critical role of taurine in the retinal excitability, several researchers have proposed the supplements of taurine-rich foods to suppress the VGB -induced retinal lesions [40,41]. As the anti-epileptic activity of taurine has also been described [42], it is conceivable that the combined use of taurine and VGB might allow for a reduced VGB dosage to minimize side effects such as the retinal toxicity. Herein, the successful preservation of visual function and retinal structure can be achieved in the VGB administered mice by taurine supplements.…”
Section: Discussionmentioning
confidence: 99%
“…However, even if GlyRs are expressed at both presynaptic and postsynaptic sites, a small number of presynaptic RNA-edited gain-of-function GlyRs even a single cluster of the non-RNA-edited GlyR α3L splice variant, which contains up to 200 receptor channels (Notelaers et al, 2012), will have a greater impact on the presynaptic membrane potential due to the much smaller volume and hence electrical capacity of this compartment compared to the somatodendritic compartment (Meier et al, 2014). Notably in this context, application of a low glycine concentration (10 μM) to hippocampal slice preparations enhanced the occurrence of epileptiform activity whereas a high glycine concentration (100 μM) attenuated recurrent epileptiform discharge (Chen et al, 2014). These divergent effects can be explained by preponderant functional impact of low glycine on presynaptic GlyRs expressed at glutamatergic terminals, resulting in facilitated glutamate release, and massive recruitment of somatodendritic GlyR activation by 100 μM glycine, resulting in tonic inhibition, respectively.…”
Section: Apobec-dependent Rna Editing In Diseasementioning
confidence: 99%